Rancang Bangun Aplikasi Pendukung Penentuan Titik Bekam Berbasis Android - Pratomo, Rizki Gumilar Nur; Sutanto, Teguh; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
The cupping is one of heritage from traditional treatment for muslims, who is now increasingly rare to be implemented. Sometimes a therapist get obstacles in determining the location of the point of a bruise and a combination of cupping point code consisting of 135 code point of cupping. Factors that influence it is the length of time needed to do a combination with point code of cupping disease based on the point of cupping. The application of a cupping therapy guide made can be applied to operating system android. It can ease a therapist to determine the location of the point of cupping to be more easily and quickly. Based on the results of the tryouts and the results of the questionnaire to 10 people therapist cupping, shows that an assessment of learnability 70,7 %, efficiency 74 %, memorability 76 %, error 72 %, satisfaction 76,7 %. Total the results of the questionnaire of 73,88 % means system has been running well. Application it may help therapist determining the location of point cupping.